Introduction of an enhanced recovery programme for total shoulder arthroplasty: report of a novel pathway - Marcus Bateman; David I Clark; Simon J Booker; Amol A Tambe; Marie L Morgan; Gareth R Davies-Jones; Edward F Ibrahim (BMJ Open Quality)
Background Enhanced recovery (ER) programmes are well established in hip and knee arthroplasty, but are not yet commonplace for total shoulder arthroplasty (TSA). This study analyses the effect of implementing an ER programme with TSA, on length of stay (LOS), functional outcome and patient satisfaction.Local problem No established programme applying ER to the specifics of upper-limb arthroplasty existed at our unit.Methods A three-cycle plan–do–study–act quality improvement methodology was applied, involving development of our multifactorial programme, a pilot phase and wider roll-out. A consecutive series of patients who underwent TSA and were enrolled in an ER programme were compared with a matched control group of consecutive patients who underwent TSA in the year before the programme started. For all patients, LOS as well as mean Oxford Shoulder Score (OSS) and Constant Score (CS) were quantified and patient satisfaction assessed.Interventions A dedicated multidisciplinary team led preoperative class involving patient education, advice and occupational therapy assessment. A standardised perioperative anaesthetic regime based on regional anaesthetic techniques with preoperative analgesic and nutritional loading was introduced. Postoperative rehabilitation was also standardised with slings for comfort only and early safe-zone mobilisation. New patient information was developed.Results 71 patients were included in matched cohorts. Mean LOS was reduced from 2.4 nights to 1.9 nights. The single night stay rate improved from 40% to 49%. Across the ER cohort, 15 less nights were required to complete same volume of surgeries as in the non-ER cohort.Parity in OSS and CS measured at 3 and 12 months after surgery were observed in both cohorts.Satisfaction was already high before ER but scores stayed the same or improved across all areas surveyed.Absolute complication rates of 9.9% in the non-ER group and 7% in the ER group were recorded.Conclusion Our ER programme benefited patients and the Trust by reducing time in hospital and improving patient satisfaction without an adverse effect on complication rate.